2010
DOI: 10.1007/s10551-010-0460-y
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Leadership Longevity on Innovation in a Religious Organization

Abstract: leadership, innovation, not-for-profit, religious organizations, empirical study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…A number of studies have shown that individuals' demographic characteristics represent a major antecedent of organizational innovation (Fritz and Ibrahim, 2010). Al-Azimi (2006) found that public sector employees in Saudi Arabia with lower levels of education but with more experience reported higher levels of innovation compared with their counterparts.…”
Section: Transformational Leadership and Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have shown that individuals' demographic characteristics represent a major antecedent of organizational innovation (Fritz and Ibrahim, 2010). Al-Azimi (2006) found that public sector employees in Saudi Arabia with lower levels of education but with more experience reported higher levels of innovation compared with their counterparts.…”
Section: Transformational Leadership and Innovationmentioning
confidence: 99%
“…Recently, there has been significant attention on examining the influence of transformational leadership on innovation in organizations. The impact of organizational leaders has attracted attention from organizational researchers (Fritz and Ibrahim, 2010). Due to their prominent positions within organizations, top leaders are uniquely capable of recognizing environmental trends and changes for initiating innovative measures to achieve organizational effectiveness (Elenkov et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, the investigation of these phenomena in developing countries suffers from a lack of research (Al-Nasani, 2008; Suifan and Al-Janini, 2017). Therefore, it is highly recommended to extend this research to developing countries (Fritz and Ibrahim, 2010;Khan et al, 2012;Qabool and Jalees, 2017). Lebanon, as one of the Arab and developing countries is a valuable model/sample.…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…The effects of transformational and change leadership on employees' commitment to change. They contended that future research should look at the linkage between other leadership theories and change success when employees make decisions about how hard they will work to implement a change [9]. The leadership and organizational change literature by exploring the relationship between manager's leadership competencies and the likelihood they will emphasize the different activities involved with effective change implementation.…”
Section: B Change Leadershipmentioning
confidence: 99%